2020
DOI: 10.1002/1873-3468.13728
|View full text |Cite
|
Sign up to set email alerts
|

Carboxy‐terminal truncations of mouse α‐synuclein alter aggregation and prion‐like seeding

Abstract: Edited by Sandro Sonnino a-synuclein (asyn) forms pathologic inclusions in several neurodegenerative diseases termed synucleinopathies. The inclusions are comprised of asyn fibrils harboring prion-like properties. Prion-like activity of asyn has been studied by intracerebral injection of fibrils into mice, where the presence of a species barrier requires the use of mouse asyn. Post-translational modifications to asyn such as carboxy (C)-terminal truncation occur in synucleinopathies, and their implications for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…Extending the study of prion-like seeding capacity of truncated αsyn fibrils to cellular and animal models is complicated due to additional extrinsic factors now involved such as modulation of cellular uptake and spread of fibrils due to truncation (194,195), trafficking to subcellular compartments (196), and structural changes to the truncated fibril due to additional PTMs; most of these variables have not been studied in relation to truncated αsyn fibrils or even typical αsyn seeding experiments. Nonetheless, cellular (22, 38, 91-93, 103, 120, 159, 189, 197, 198) and animal (133,159,189,199) experiments using fibrils containing truncated αsyn have shown some similar findings to in vitro studies.…”
Section: Fibrils Containing Truncated αSyn Have Strain-like Variationmentioning
confidence: 78%
See 4 more Smart Citations
“…Extending the study of prion-like seeding capacity of truncated αsyn fibrils to cellular and animal models is complicated due to additional extrinsic factors now involved such as modulation of cellular uptake and spread of fibrils due to truncation (194,195), trafficking to subcellular compartments (196), and structural changes to the truncated fibril due to additional PTMs; most of these variables have not been studied in relation to truncated αsyn fibrils or even typical αsyn seeding experiments. Nonetheless, cellular (22, 38, 91-93, 103, 120, 159, 189, 197, 198) and animal (133,159,189,199) experiments using fibrils containing truncated αsyn have shown some similar findings to in vitro studies.…”
Section: Fibrils Containing Truncated αSyn Have Strain-like Variationmentioning
confidence: 78%
“…C-truncation of αsyn increases aggregation in vivo as well; in addition to the structural aspects, removal of the C-terminus may further enhance aggregation in a cellular milieu through impaired αsyn degradation due to loss of consensus motifs for ubiquitin ligases and chaperone mediators of autophagy (169)(170)(171), and through loss of normally protective C-terminal interactions such as binding of oxidized dopamine (172,173). Although not as numerous as the in vitro studies, experiments have been conducted demonstrating that C-truncation of αsyn promotes aggregation into pathologic inclusions in cultured cells and animal models (22,130,159,(174)(175)(176)(177)(178)(179)(180)(181)(182)(183). These same studies often demonstrated toxic consequences from Ctruncation of αsyn that will be discussed further.…”
Section: Truncation Of αSyn Increases Aggregation In Cultured Cells Amentioning
confidence: 99%
See 3 more Smart Citations